Deficit-Lesion Correlations in Syntactic Comprehension in Aphasia - Caplan, David (Brain Lang, 2015)
The effects of lesions on syntactic comprehension were studied in thirty one people with aphasia (PWA). Participants were tested for the ability to parse and interpret four types of syntactic structures and elements -- passives, object extracted relative clauses, reflexives and pronouns – in three tasks – object manipulation, sentence picture matching with full sentence presentation and sentence picture matching with self-paced listening presentation. Accuracy, end-of-sentence RT and self-paced listening times for each word were measured. MR scans were obtained and analyzed for total lesion volume and for lesion size in 48 cortical areas. Lesion size in several areas of the left hemisphere was related to accuracy in particular sentence types in particular tasks and to self-paced listening times for critical words in particular sentence types. The results support a model of brain organization that includes areas that are specialized for the combination of particular syntactic and interpretive operations and the use of the meanings produced by those operations to accomplish task-related operations.